A Review of New Understanding of the Role of Individual Structure within the Head of Dolphins in Formation of Biosonar Signal and Beam - Au, Whitlow; Wei, Chong (2017)
New data obtained in the past five years have significantly increased our understanding of sound propagation within the heads of dolphins. Results of Au et al. [1] reinforce the notion that source intensity is the primary factor controlling the peak and center frequencies of biosonar clicks which in turn affect the duration and the bandwidth of clicks. Finite element simulation in the vertical plane of broadband acoustic signals propagation in the head of the Baiji or Lipotes vexillifer [2] and ongoing simulation with Phocoena phocoena and Tursiops truncatus have shown that the air sacs and skull are the major contributor on the shape of the beam and that the melon has a minimum role in the focusing of the signals. The small acoustic impedance gradient in the melon does not allow sufficient ray bending to take place even if the melon is deformed slightly. Comparing the biosonar signals used by free-swimming and stationary dolphins in a pen showed a similar tendency of dolphins, like bats, to emit longer duration signals with greater bandwidth while free swimming. The wide off-angle measurements of the biosonar beam of Tursiop truncautus revealed an internal reflection as the cause of a 2nd pulse in the signals.